Complete clot ingestion with cyclical ADAPT increases first-pass recanalization and reduces distal embolization. (4th February 2019) - Arslanian, Rose A; Marosfoi, Miklos; Caroff, Jildaz; King, Robert M; Raskett, Christopher; Puri, Ajit S; Gounis, Matthew J; Chueh, Ju-Yu
Abstract : Background: Evidence is mounting that first-pass complete recanalization during mechanical thrombectomy is associated with better clinical outcomes in patients presenting with an emergent large vessel occlusion. We hypothesize that aspiration achieving complete clot ingestion results in higher first-pass successful recanalization with quantitative reduction in distal emboli. Methods: A patient-specific cerebrovascular replica was connected to a flow loop. Occlusion of the middle cerebral artery was achieved with clot analogs. Independent variables were the diameter of the aspiration catheter (0.054–0.088in) and aspiration pattern (static versus cyclical). Outcome measures were the first-pass rates of complete clot ingestion, the extent of recanalization, and the particle-size distribution of distal emboli. Results: All aspiration catheters were successfully navigated to the occlusion. Complete clot ingestion during aspiration thrombectomy resulted in first-pass complete recanalization in every experiment, only achieved in 21% of experiments with partial ingestion (P<0.0001). Aspiration through the large bore 0.088in device resulted in the highest rates of complete clot ingestion (90%). Cyclical aspiration (18–29 inHg, 0.5 Hz) significantly increased the rate of complete clot ingestion (OR21 [1.6, 266]; P=0.04). In all experiments, complete clot ingestion resulted in fewer and smaller distal emboli. Conclusions: Complete clot ingestion results in fewer distal emboli and the highest rates of first-pass complete recanalization. The rate of complete ingestion during aspiration thrombectomy is a function of both the inner diameter of the aspiration catheter and use of cyclical aspiration.